2012
DOI: 10.1371/journal.pone.0038706
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitochondria- and Endoplasmic Reticulum Stress-Mediated Autophagy Augments Temozolomide-Induced Apoptosis in Glioma Cells

Abstract: Autophagy is a crucial process for cells to maintain homeostasis and survival through degradation of cellular proteins and organelles, including mitochondria and endoplasmic reticula (ER). We previously demonstrated that temozolomide (TMZ), an alkylating agent for brain tumor chemotherapy, induced reactive oxygen species (ROS)/extracellular signal-regulated kinase (ERK)-mediated autophagy to protect glioma cells from apoptosis. In this study, we investigated the role of mitochondrial damage and ER stress in TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 48 publications
4
79
1
Order By: Relevance
“…Induction of autophagy by TMZ has been documented in glioma cell lines and surgical specimens (11,12). In agreement with this, the current results showed that treatment with 100 µM TMZ induced autophagy as shown by a significant increase of AVOs and enhanced cleavage of LC3B (Fig.…”
Section: Tmz Treatment Induces Autophagy In Gliomasupporting
confidence: 90%
See 1 more Smart Citation
“…Induction of autophagy by TMZ has been documented in glioma cell lines and surgical specimens (11,12). In agreement with this, the current results showed that treatment with 100 µM TMZ induced autophagy as shown by a significant increase of AVOs and enhanced cleavage of LC3B (Fig.…”
Section: Tmz Treatment Induces Autophagy In Gliomasupporting
confidence: 90%
“…Induction of autophagy by TMZ has been documented in glioma cell lines and surgical specimens, and inhibition of autophagy augments TMZ-induced apoptosis in glioma cells (11,12). However, the molecular mechanism by which TMZ induces autophagy is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…45 Moreover, our data are consistent with the findings of other studies that autophagy could be triggered by ER stress. 46 Therefore, ER stress may cause autophagy to either protect or kill cells in different environments. However, the precise role of autophagy in ER stress is far from clear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that high doses of temozolomide (1 mmol/L) and POH (1 mmol/L) activate cell death through ER stress pathway (5,31). To compare the efficacy of NEO212 and temozolomide, equimolar concentrations of these drugs were analyzed for expression of GRP78, CHOP, and cleaved PARP, proteins responsible for cytotoxicity initiated by ER stress.…”
Section: Neo212 Induces Glioma Cell Cytotoxicity Through Several Pathmentioning
confidence: 99%